I love you to the moon and back all year long - Hepworth, Amelia; Warnes, Tim (Wilton, CT Tiger Tales, 2023)
A mother bear and her cub celebrate their love that stays strong through the passing of the seasons, all year long.
112551
Keywords: Parent and child -- Juvenile fiction; Love -- Juvenile fiction; Seasons -- Juvenile fiction; Juvenile Fiction -- Social Themes -- Emotions & Feelings; Juvenile Fiction -- Family -- Parents; Picture books; Stories in rhyme